Uma abordagem para a decomposição de processos de negócio para execução em nuvens computacionais - Povoa, Lucas Venezian (Universidade Federal de São Carlos, 2014)
Business Process Management emerged as a means for managing and improving business processes. However providing efficient business processes can demand high costs due to the need of software, hardware, and technical support. Cloud Computing emerged as a means for providing a fast and cheap way of acquiring computational resources in a pay-per-use manner, and can be employed for achieving efficient business processes with low costs. However, due to safety requirements, certain data or activities of a business process should be kept within the user premises, while others can be allocated to a cloud. This master dissertation presents a generic approach for decomposing business process taking into account costs, performance and safety requirements, thus granting greater reliability in the use of cloud resources. This approach is illustrated by means of a case study in the Healthcare domain.
Keywords: Ciência da computação; Gerenciamento de processos de negócio; Computação em nuvem; Decomposição de processos de negócio; Modelo baseado em grafos; Grafos; Business processes; Cloud computing; Graph; BPMN; WS-BPEL; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO